EXPLORING THE BENEFITS OF ARTIFICIAL INTELLIGENCE TOWARDS ENSURING A SUSTAINABLE AGRICULTURAL DEVELOPMENTS IN NIGERIA - Kayode David KOLAWOLE (International Journal of Social and Educational Innovation)
This paper looks at the relationship between artificial intelligence (AI) and agricultural developments in Nigeria. The place of Agriculture in Nigeria’s economy is of high premium. In Nigeria, agriculture has traditionally been a significant contributor to the livelihoods of its population. Over 60-70% of the population relies on agriculture directly or indirectly for their livelihoods. This percentage includes smallholder farmers, agricultural laborers, agribusiness workers, and those involved in related sectors such as food processing and distribution. As a nation keying into fast growing technology space. Nigeria stands to benefit immensely from the integration of AI technologies into its agricultural sector. The study focused on overview of the current state of agriculture in Nigeria, the trend of agriculture practice, the key challenges such as climate change, environmental degradation, limited access to finance, as well as consider the benefits of AI to the agricultural sector.